Complement Factor H-Related 3 Enhanced Inflammation and Complement Activation in Human RPE Cells - Schäfer, Nicole; Rasras, Anas; Ormenisan, Delia M.; Amslinger, Sabine; Enzmann, Volker; Jägle, Herbert; Pauly, Diana (Frontiers in Immunology, 2021)
Complement Factor H-Related 3 (FHR-3) is a major regulator of the complement system, which is associated with different diseases, such as age-related macular degeneration (AMD). However, the non-canonical local, cellular functions of FHR-3 remained poorly understood. Here, we report that FHR-3 bound to oxidative stress epitopes and competed with FH for interaction. Furthermore, FHR-3 was internalized by viable RPE cells and modulated time-dependently complement component (C3, FB) and receptor (C3aR, CR3) expression of human RPE cells. Independently of any external blood-derived proteins, complement activation products were detected. Anaphylatoxin C3a was visualized in treated cells and showed a translocation from the cytoplasm to the cell membrane after FHR-3 exposure. Subsequently, FHR-3 induced a RPE cell dependent pro-inflammatory micro-environment. Inflammasome NLRP3 activation and pro-inflammatory cytokine secretion of IL-1ß, IL-18, IL-6 and TNF-α were induced after FHR-3-RPE interaction. Our previously published monoclonal anti-FHR-3 antibody, which was chimerized to reduce immunogenicity, RETC 2 ximab, ameliorated the effect of FHR 3 on ARPE-19 cells. Our studies suggest FHR-3 as an exogenous trigger molecule for the RPE cell “complosome” and as a putative target for a therapeutic approach for associated degenerative diseases.